American future : a history from the founding fathers to barack obama - Schama, Simon ([S.l.] : Vintage Books USA, 2010)
The American Future traces the history of a country whose most enduring trait is its capacity for self-renewal, especially at times of disaster. Examining issues of power, race and immigration, religious fervour and prosperity, this masterful portrait of the world's most controversial superpower looks backwards and forwards to understand why now, more than ever, the fate of America, and by extension the rest of the world, is hanging in the balance.
International Edition.